Overview of Macro Nutrient Intake and Nutritional Status of Students at the Putri Hidayatullah Islamic Boarding School, Ternate City: Overview of Macro Nutrient Intake and Nutritional Status of Students at the Putri Hidayatullah Islamic Boarding School, Ternate City - Abubakar, Hisdawati; Willi Helm, Yohannes; Nofiandri; Fadila, (International Journal of Scientific Research and Management (IJSRM), 2021)
Adolescents are one of the nutritionally vulnerable groups. At this time, adolescents enter the second phase of rapid growth and then physical growth declines as young adults enter. Problems that arise in adolescents are undernutrition and overnutrition. One that is related to nutritional status is nutrient intake which is very influential on a person's nutritional status. Nutrient intake is influenced by eating habits and eating patterns of adolescents themselves. The purpose of this study was to determine the description of macronutrient intake and nutritional status at the Putri Hidayatullah Islamic Boarding School, Ternate City. The type of research used is descriptive research. The sampling technique used total sampling with a total sample of 29 people. The tools used were Microtoise, Bathroom Scale and form food recall 24. The results showed that the intake of macronutrients, as many as 28 people (96.6%) with less energy intake, 29 people (100.0%) with less protein intake, 16 people (55.2%) with more fat intake and 26 people (89.7%) with less carbohydrate intake. There were 25 people (86.2%) with normal nutritional status. It was concluded that from the results of the respondents had less protein intake and most had less energy and carbohydrate intake. On the other hand, most of these teenagers have good fat intake with normal nutritional status.